(untitled) (Jurnal Manajemen Bisnis, 2026)
Transformational leadership is key to facing the increasingly complex VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) challenges of the modern era. This study aims to analyze the role of transformational leadership in addressing VUCA challenges at PT Telkom Kediri Branch. The method used is a case study with a qualitative approach, where data is collected through in-depth interviews and observations. The results show that leaders who apply a transformational leadership style are able to create an adaptive work environment, increase employee motivation, and encourage innovation. In addition, leaders also play a role in building effective communication and collaboration between teams, which are very important in facing complexity. This study provides insights for other organizations in developing effective leadership strategies amidst VUCA challenges.